Identification of Ferroptosis-Related Prognostic Signature and Subtypes Related to the Immune Microenvironment for Breast Cancer Patients Receiving Neoadjuvant Chemotherapy - Xu, Yuhao; Du, Yaoqiang; Zheng, Qinghui; Zhou, Tao; Ye, Buyun; Wu, Yihao; Xu, Qiuran; Meng, Xuli (Frontiers in Immunology, 2022)
Purpose: To identify molecular clusters associated with ferroptosis, and to develop a ferroptosis-related signature for providing novel potential targets for the recurrence-free survival and treatment of breast cancer. Methods: Ferroptosis-related genes signature was constructed by univariate and multivariate Cox regression and least absolute shrinkage and selection operator (lasso). Receiver operating characteristic curves, Kaplan–Meier survival analysis, Principal component analysis and univariate and multivariate Cox regression analyses in the train and test cohorts were used to evaluate the application of this signature. Quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) was employed to detect the expression of FRGs in the model. Furthermore, the correlations between the signature and immune microenvironment, somatic mutation and chemotherapeutic drugs sensitivity were explored. Results: Internal and external validations affirmed that relapse-free survival differed significantly between the high-risk and low-risk groups. Univariate and Multivariate Cox regression analysis indicated that the riskScore was an independent prognostic factor for BRCA. The AUCs for predicting 1-, 2-, and 3-year survival in train and test cohorts were satisfactory. Significant differences were also found in immune microenvironment and IC50 of chemotherapeutic drugs between different risk groups. Furthermore, wedivided patients into three clusters based on 18 FRGs to ameliorate the situation of immunotherapy failure in BRCA. Conclusions: The FRGs signature functions as a robust prognostic predictor of immune microenvironment and therapeutic response, with great potential to guide individualized treatment strategies in the future.